A review of the automatory for strategy and policy study organizations for state management - Nguyen Thi Minh Hanh; Nguyen Thi Thuy Linh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Organizations that research strategies and policies in service of state management in ministries are units that perform research tasks in order to provide a scientific basis for the formulation of strategies and policies for state management. As a constituent part of the national system of S&T organizations, strategic and policy research organizations in service of state management are also subject to implementation of the autonomy mechanism, from the autonomy mechanism according to the provisions of Decree No. 115/2005/ND-CP dated September 5, 2005 of the Government, to the autonomy mechanism in accordance with the Government's Decree No. 54/2016/ND-CP dated June 14, 2016. The following article reviews the implementation of the autonomy mechanism for strategic and policy research organizations in service of state management over the past 15 years. Code: 2201040